Prototipe Sistem Evaluasi Integratif Empat Keterampilan Bahasa Arab: Desain, Pengembangan, dan Uji Kelayakan - Dian Ramadhani Abdullah; Milda Damayanti; Nurul Hikmah; Cici Zaskia; Nizar Nizar; Herdah Herdah (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2026)
The evaluation of Arabic language learning that has been implemented tends to be partial and has not been able to measure the four language skills, namely maharah al-istima', maharah al-kalam, maharah al-qira'ah, and maharah al-kitabah, in an integrated and comprehensive assessment system. This study aims to design, develop, and test the feasibility of an integrative evaluation system prototype for four Arabic language skills as a solution to these limitations. The method used is Research and Development (R&D) with the ADDIE model, limited to the development and expert validation stages. Data were collected through needs interviews, documentation studies, and a four-point Likert scale expert validation questionnaire involving Arabic language learning experts and educational technology experts. The validation results indicate that the developed integrative evaluation system prototype meets the feasibility criteria in terms of validity, reliability, practicality, effectiveness, and comprehensiveness, and is therefore declared suitable for use as an Arabic language learning assessment tool. The prototype includes written test instruments, oral tests, observation sheets, portfolio assessments, and scoring rubrics designed to holistically measure students' Arabic language competence. This study implies the need for renewal of a more integrative and technology-based Arabic language evaluation system to support the continuous improvement of Arabic language learning quality.